New species of the genus Gnathochorisis Förster (Hymenoptera: Ichneumonidae: Orthocentrinae) from the Neotropical Region - Humala, Andrei E. (Zootaxa, 2017)
The Neotropical species of the genus Gnathochorisis (Ichneumonidae: Orthocentrinae) are reviewed, seven species: G. enodis sp. nov., G. khalaimi sp. nov. from Mexico, G. intercalaris sp. nov., G. punctata sp. nov., G. rufa sp. nov., G. rufithorax sp. nov. from French Guiana, and G. dilleri sp. nov. from Peru are described and illustrated, and one species G. laticincta comb. nov. is transferred from the genus Symplecis. A key to the Neotropical Gnathochorisis species is provided.